TYPICAL CURRICULUM OF UKRAINIAN AS A FOREIGN LANGUAGE FOR PREPARATORY FACULTIES OF HIGHER EDUCATIONAL ESTABLISHMENTS IN UKRAINE: THEORY AND PRACTICE OF DEVELOPMENT - Halyna Ivanyshyn (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article describes the standard curriculum of normative discipline "Ukrainian language as a foreign one" worked out by coworkers of Linguistics Department of Ivano-Frankivsk National Medical University for preparatory faculties of ukrainian higher educational institutions. The purpose, principles, approaches, content and structure of the program are determined. All of the above mentioned components help to implement the concept of foreign students training of Ukrainian language at universities in Ukraine. The curriculum meets the general educational standards of Ukrainian language and determines the foreign students' level of linguistic and communicative competence within the speech activity: speaking, listening, reading and writing. The content of teaching defined in the curricullum, is based on general and special linguodidactic principles. The authors of the curriculum offer to implement the process of foreigners' language education at preparatory faculties in the unity of the communicative, adaptive and general scientific approaches. The program defines the main strategic directions of education - content lines (speech, language, socio-cultural, active, or strategic) that help students to achieve the required level of communicative competence sufficient for communication and learning, and professional growth.